STUDI PERAN EVALUASI MANAJEMEN DALAM OPTIMALISASI LAYANAN BIMBINGAN DAN KONSELING DI SEKOLAH - Berta Charolina Balqis; Cahya Emeliasari; Adianna Muthia Susanto; Elisabeth Christiana (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
This study aims to identify how management evaluation contributes to the management and improvement of guidance and counseling services in schools. This study uses a qualitative approach based on literature studies. In an activity, a re-evaluation is needed to see whether the implementation is in accordance with the initial planning, therefore an evaluation is needed. Evaluation in guidance and counseling management is present as a forum to assess the progress of a BK program. The results show that data-based management evaluation can improve the quality of BK services, strengthen support for students, and optimize the role of counselors in schools. These findings provide strategic insights for educational administrators, counselors, and policy makers for the implementation of more effective management evaluation, supporting the development of BK services in a sustainable manner. Not only that, but the evaluation also involves a detailed analysis of the results that have been carried out to ensure that future implementation is smoother and has minimal shortcomings. This study provides practical recommendations for the implementation of more effective management evaluation in supporting the development of BK services in schools.